STRATEGI DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG DALAM UPAYA MENGEMBANGKAN PARIWISATA KOTA SEMARANG - Mayang Vini Setya; Sulistyowati .; Warsito . (Journal of Politic and Government Studies, 2017)
Tourism is one of the sector that has an important role to succeedregional autonomy, where development and resource utilization and tourism potential isneeded. The high tourism potential of Semarang City with 64 tourist attractions should beable to make Semarang City as the tourism destination city and not just a transit city.Department of Culture and Tourism of Semarang City as regional device organization hasduties and responsibilities to carry out government affairs particularly tourism affairs.Therefore, the purpose of this research was to describe the phenomenon or the actualcircumstances which occured about how the strategy of Department of Culture andTourism of Semarang City in an effort to develop tourism in Semarang City. The researchwas using descriptive qualitative research method with documentation and interview asthe data collection technique. Targets of the research were government, private, andcommunity who participated in tourism development management in Semarang City. Themain focus of this research was the context of the strategy implementation of Departmentof Culture and Tourism of Semarang City in an effort to develop tourism in SemarangCity, tourism marketing of Semarang City, including the role of society as well as the roleof private sector in tourism development of Semarang City.Keywords : Management, Tourism, Development, Strategy